The Connection Between Essential Running Techniques and Long Jump Performance Indicators in Elementary School Learners Aged 10-11 Years - Lilis Lasma Suriani. S. (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2024)
The purpose of the study. The primary objective of this research is to analyze the link between running technique proficiency and long jump performance in 10 to 11-year-old elementary students. Materials and methods. A sample of 28 male students, aged 10 to 11 years, was selected for this study. A cross-sectional research design was utilized to investigate the relationship between basic running techniques and long jump performance in this demographic. Pearson correlation analysis was conducted to assess the association between running methodologies and long jump effectiveness. The results of this analysis determined the strength and direction of the relationship between the two variables. Results. The analysis yielded a significant correlation coefficient of r= 0.917, with a p-value of 0.000<0.005, indicating a strong positive correlation. This finding suggests that students' skills in body alignment, arm swing, and leg coordination in running are closely related to their ability to generate the power, speed, and control necessary for superior long jump performance. Conclusions. This study provides empirical support for the claim that proficiency in fundamental running techniques, including body alignment, arm swing, and leg coordination, correlates significantly with improved long jump performance in 10 to 11-year-old elementary school students.